Recent developments in chemical vapor deposition of 2D magnetic transition metal chalcogenides - Tang, Bijun (2022)
In recent years, two-dimensional (2D) magnetic transition metal chalcogenides (TMCs) have attracted tremendous research interests thanks to their intriguing properties that are essential in developing future electronic and spintronic devices in this modernizing era. This review aims to introduce recent developments in the preparation of 2D magnetic TMCs, especially chromium and iron-based chalcogenides, their structures, as well as the related intriguing magnetic phenomena. First, the common crystal structures of magnetic TMCs including both layered and nonlayered structures are introduced. Various chemical vapor deposition strategies for synthesizing 2D magnetic TMCs are then introduced with emphasis on the key synthesis parameters. Moreover, the intriguing physical properties associated with 2D TMCs such as magnetic anisotropy, thickness, and phase-dependent magnetic response as well as stability are summarized. Last but not least, challenges and future research directions are briefly discussed in light of recent advances in the field.